Association between intra-articular hyaluronic acid injections in delaying total knee arthroplasty and safety evaluation in primary knee osteoarthritis: analysis based on Health Insurance Review and Assessment Service (HIRA) claim database in Republic of Korea - Jun-Gu Park; Juho Sim; Seung-Beom Han (BMC Musculoskeletal Disorders)
Abstract Background The prevalence of knee osteoarthritis (KOA), a progressive degenerative disease, is gradually increasing, and it is a progressive degenerative disease. In patients with mild-to-moderate KOA, intra-articular hyaluronic acid (IA-HA) has been shown to be an effective non-operative treatment option that can provide significant pain relief and symptom improvement by increasing intra-articular viscoelasticity. This study aimed to evaluate the efficacy of IA-HA injections in delaying total knee arthroplasty (TKA) and the safety of IA-HA according to IA-HA type and combination with intra-articular corticosteroid (IA-CS) using a large health insurance claim database. Methods For this retrospective cohort study, the study population included patients aged ≥ 50 years with a first diagnosis of KOA between 2009 and 2014, who underwent TKA by 2020, using the Health Insurance Review and Assessment Service claim database in Republic of Korea. IA-HA injections were categorized as single or multiple injection regimen agents. Cox proportional hazard models estimated hazard ratios (HR) for TKA risk, adjusted for covariates. Logistic regression assessed the occurrence of adverse events after IA-HA administration. Results In all, 36,983 patients were included. Patients who received IA-HA injections had a significantly longer time to TKA compared to those who did not (mean delay of approximately 1 year). The IA-HA group had a significantly lower risk of TKA (HR: 0.61, 95% CI: 0.60–0.62) than non-IA-HA group after adjusting for covariates, which included age, sex, medical history, number of hospital beds, and CS injection. Single injection IA-HA regimen agents showed the longest time to TKA and lowest risk (HR: 0.56, 95% CI: 0.53–0.59). TKA risk decreased with the number of IA-HA cycles. Adverse events occurred in 6.7% of IA-HA cases without CS, with very low incidence of infection. Multiple injection regimen agents (multiple injection regimen 7.0% vs. single injection regimen 3.6%) and concurrent IA-CS use (concurrent IA-CS use 13.9% vs. IA-HA only 6.7%) were associated with higher infection risk. Conclusion IA-HA injections were associated with a significant delay in TKA among patients with KOA. Single-injection regimen agents had the lowest TKA risk. Infection risk increased with multiple injections and concurrent IA-CS use. These findings could suggest the use of IA-HA as an effective non-operative intervention option for managing KOA and delaying TKA. Careful selection of IA-HA type and consideration of concurrent IA-CS use could play a role in delaying the time to TKA and reducing complications.